Analisis Vegetasi Gulma Pada Perkebunan Karet (Hevea brasiliensis Mull.Arg.) di Kecamatan Batang Kapas, Kabupaten Pesisir Selatan - Rista Novalinda; Zuhri Syam; - Solfiyeni (Jurnal Biologi Universitas Andalas, 2014)
Vegetation analysis of weeds at rubber plantation (Hevea brasiliensis Mull.Arg.) at Batang Kapas, Pesisir Selatan, was carried out from March to April 2013. The weeds were sampled purposively using plot quadrat method at three and six years old of rubber plantations. There were totally 13 families, 23 genera dan 27 species of weeds found in the two types of rubber plantations. The two locations were dominated by different species of weeds. Borreria alata has the highest Summed Dominance Ratio (SDR) at three years and Scleria sumatrensis at six years old of rubber  plantations. Diversity indices were relative moderate (2,17 at three years old and 2,2 at six years old rubber plantations) in both locations and species similarity between the two location were low (45,7%).